Sosialisasi Tentang Akreditasi Rumah Sakit Pada Mahasiswa Kesehatan & Staf Rumah Sakit - Oktavy Budi Kusumawardhani; Ahmad Supriyanto; Iwan Setiawan (Edumedia Solution, 2022)
Accreditation demonstrates a hospital's real commitment to improving the safety and quality of patient care, ensuring that the service environment is safe and the hospital strives to reduce risks for patients and hospital staff. The purpose of this study was to determine the understanding of hospital accreditation for health students and hospital personnel. For this method of service, we use zoom webinars and target health students and hospital staff. Health students and hospital personnel understand and can carry out hospital accreditation to improve the safety and quality of patient care. Research can increase knowledge and understanding of hospital accreditation for health students and hospital staff.